Advances in immunotherapeutic strategies for colorectal cancer commentary on: tumoral immune cell exploitation in colorectal cancer metastases can be targeted effectively by anti-CCR5 therapy in cancer patients by Halama et al. Issue 1 (December 2016) - Deming, Dustin
Abstract Colorectal cancer is a leading cause of cancer-related death in the United States, despite recent advances in treatment strategies. The immune system has been implicated in the pathogenesis of colorectal cancer, with numerous studies identifying either antagonistic or pro-tumorigenic effects of infiltrating immune cells. Therapeutic strategies harnessing the immune system to target cancers have evolved expediently over the last 5 years, especially the use of checkpoint inhibitors. Recently, a subset of patients whose colorectal cancers harbor a deficiency in mismatch repair proteins have demonstrated dramatic and durable response to checkpoint blockade. Unfortunately, the vast majority of colorectal cancers are mismatch repair proficient and resistant to these inhibitors. The tumor microenvironment has been implicated in the resistance to checkpoint block and ways to overcome these resistance mechanisms would be a major advance for the treatment of colorectal cancer. Here we provide commentary on a manuscript from Halama et al. examining CCL5/CCR5 as an immune biomarker and the potential role of anti-CCR5 agents for the treatment of patients with colorectal cancer.